The Effectiveness Of Using Digital Comic-Based Media In Increasing Social Studies Learning Outcomes - Ramdani, Mamur; Mulyana, Eldi; Nopharipaldi Rohman, Slamet; Widyanti, Triani; Tetep; Supriyatna, Asep; Nugraha, Yopi (RISTEC : Research in Information Systems and Technology, 2021)
This resea rch is motivated by the low socia l studies learning outcomes that occur in students in cla ss VIII SMP Islam As-Syarief. The low socia l studies lea rning outcomes a re caused by severa l factors, one of which is the use of socia l studies learning methods and media that a re less attractive and do not invite students to be actively involved in the learning process. Researchers tried to use comic-based worksheets for learning media a imed at improving socia l studies learning outcomes. The method used is a quasi-experimenta l resea rch design with a nonequivalent [pre-test and post-test] control group design. The population in this study were eighth grade students of SMP Islam As-Syarief. The samples taken were cla ss VIII-C and VIII-E. Data was obta ined by means of tests (pre-test and post-test), and observation sheets. Data analysis was performed using the Lilliefors norma lity test (Kolmogorov-Smirnov and Shapiro-Wilk), the Mann Whitney test, and the normalized Ga in test. The results showed that lea rning using comic- based worksheets wa s effective in improving socia l studies lea rning outcomes for students, it wa s based on the avera ge va lue of socia l studies learning outcomes after treatment wa s higher than before. The conclusion of this study is that comic-ba sed worksheets are effective in improving socia l studies lea rning outcomes for class VIII students of SMP Islam As-Syarief.